(untitled) (Research, Society and Development, 2022)
Sexually Transmitted Infections (STIs) are diseases that have their spread facilitated, mainly by sexual practice without the use of condoms. They cause a worldwide health problem whose consequences range from infertility problems, cancer development, pregnancy complications, fetal death or infection and even psychological problems that are affecting more and more young people and adolescents. Therefore, the present study aimed to assess the understanding of STIs by a group of high school students from the public school system in Pernambuco, and based on the information obtained from this survey, to obtain a direction for awareness-raising actions. that aim to resolve doubts, as well as combat misinformation about this issue among these young people. The results showed that only 54% of these students stated that they had knowledge about STIs and AIDS; 74% of the students answered the use of condoms as a condom method; 22% did not know how to give an opinion about the accessibility there are preventive methods; most of these students reported that they do not see positive aspects about contracting STIs and found it beneficial for us to disclose about STIs. Based on the above, we can conclude that despite the advent of the internet, and the large amount of information we have daily access to on this topic, the critical and planned orientation of these materials is still extremely important, since only knowing the preventive methods, STIs and their consequences are not done enough to opt for a healthy attitude.